RE-OS ISOTOPIC VARIATIONS IN CARBONACEOUS PELITES HOSTING THE DULUTH COMPLEX: IMPLICATIONS FOR METAMORPHIC AND METASOMATIC PROCESSES ASSOCIATED WITH MAFIC MAGMA CHAMBERS - Ripley E.M.; Park Y.R.; Lambert D.D.; Frick L.R. (My University, 2001)
Previous mineralogic and isotopic studies of sulfide mineralization in the 1.1 Ga Duluth Complex have suggested that sulfur, and possibly metals, have been derived from Proterozoic sedimentary country rocks. The Re-Os isotopic system offers great potential in the evaluation of crustally derived metals in magmatic ore-forming processes, but an understanding of the mechanisms that could cause isotopic variations in country rock contaminants is a prerequisite. A suite of sulfidic and carbonaceous pelitic rocks of the Virginia Formation (country rock to the Duluth Complex), ranging from unmetamorphosed through strongly recrystallized and partially melted xenoliths, have been analyzed for their Os isotopic composition. Sulfide mineral separates (mainly pyrrhotite), kerogen-graphite isolates, and whole rocks, were analyzed. Whole rocks, kerogen, and graphite from metamorphosed samples plot between 1.85 Ga and 1.1 Ga chondritic reference isochrons. Sulfide separates from all metamorphosed samples plot nearer the chondritic 1.1 Ga reference isochron and require exchange with a fluid or melt characterized by a chondritic Os isotopic composition (potentially derived from the Duluth Complex). Devolatilization and partial melting may perturb isotopic systematics when accompanied by the loss of Re- and Os-bearing fluids. These processes could in part explain the scatter in isotopic values found in kerogen and metamorphosed whole rocks. However, metasomatic addition of Os via interaction with a fluid or melt is required to explain the sulfide isotopic ratios and is consistent with sulfide minerals being more susceptible to Os exchange with a fluid than kerogen. The relative ease with which pyrrhotite may be reset during fluid interaction, as well as the variable degrees of exchange shown by kerogen/graphite, suggest that a knowledge of the petrologic and isotopic evaluation of country rocks is necessary before a meaningful assessment of the isotopic variations found in igneous rocks or associated ore deposits can be undertaken.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой